Biomedical researches and ethics - DİNÇ, Gülten (Cerrahpaşa Medical Journal, 2014)
The parallel faced problems since 20th century; topics of science, research and publication ethics have been started to take seriously nowadays. Especially in biomedical field, lots of historical examples for “putting society’s benefits before the individual’s benefits” take place among its reasons. In this article, under the light of historical improvement and international declarations, the topics of improper research and publication ethics of biomedical researches have been followed up.